Mixed Research Methods in Adult Education –Why Combining Methods Is (Not) Reasonable? - Trusz, Sławomir (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
Is it possible to combine quantitative and qualitative methodologies in a single study in adult education? Extreme proponents of the quantitative versus qualitative approach maintain that it is not. They argue that the differing perspectives necessitate the analysis of two distinct research subjects. In contrast, moderate researchers argue that such triangulation is possible, as quantitative and qualitative data can address the same subject. In this case, the research perspectives are complementary, leading to enriched results and more nuanced conclusions. Using the example of stereotype threat amongseniors, this paper demonstrates how quantitative-qualitative or qualitative-quantitative researchcan be conducted. The proposed procedures are illustrated with analyses based on both quantitative and qualitative data.